Microbial Pack as Probiotic Supplements to Improve Gut Immunity for Homeostasis (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Probiotics are live microorganisms that, when administered or present in sufficient quantities,have beneficial effects on host health in increased lifespan. Probiotic supplements must be tested to determinetheir efficacy as a non-chemical approach to promoting health and well-being. Objective: Our research workfocuses on determining the molecular impact of probiotic administration on homeostasis and immunity.Methods: Shrimpswere administered with recommended doses of microbial pack containing Bacillus speciesand Rhodococcus species and the fermentation was carried at 37Â°C for 72 h under microaerophilic condition.The parameters such as pH, microbial load, acidity, and concentration of reducing sugar had been measured.Results: This probiotic pack when used either alone or in combination with traditional dairy starter, significantlyimproved the nutritional properties and the shelf life of the product. Conclusion: The current work will be usefulin developing novel functional foods based on these unique probiotic properties.